Effect of Green Marketing, Brand Image, Brand Equity, and Customer Orientation on Buying Interest in Zorlien Light Emitting Diode Products Moderated by Internet Technology (Study on Students at the Universitas 17 Agustus 1945 Jakarta) - Phamendyta Aldaning Azaria; Nurika Haerul Utami (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze effect of green marketing, brand image, brand equity, and customer orientation on buying interest in Zorlien Light Emitting Diode products moderated by internet technology, study on Students at the Universitas 17 Agustus 1945 Jakarta. This type of research is explanatory research. The population in this study are consumers who have purchased Zorlien Light Emitting Diode products. The sample in this study are 97 respondents with the criteria of every consumer met and who had bought or had not used but already had a Zorlien Light Emitting Diode product. The type of data used in this research is quantitative data. Data analysis are tested with inner model measurement through coefficient of determination and value of path coefficients. Based on the results of the study, it shows that green marketing has significant effect on buying interest, brand image has insignificant effect on buying interest, brand equity has significant effect on buying interest, customer orientation has insignificant effect on buying interest, and internet technology has insignificant effect on buying interest. Moderation of internet technology in green marketing has insignificant effect on buying interest. Moderation of internet technology on brand image has insignificant effect on buying interest. Moderation of internet technology on brand equity has significant effect on buying interest. Moderation of internet technology on customer orientation has insignificant effect on buying interest.